The one you want : a novel - Ryan, Jennifer, 1973- (Avon, an imprint of HarperCollinsPublishers, 2022)
"Returning home to act as maid of honor for her best-friend-forever Maggie, Rose is stunned when she discovers that Maggie's husband-to-be is a man with whom she had a one-night stand and, as the big day approaches, must make one of biggest decisions of her life"--